Necesidad de establecer Senderización y determinar la respectiva Señalética en el atractivo turísticLa Laguna Chinchilla” de la Parroquia Manú del Cantón Saraguro de la Provincia de Loja - Alvarado Jaramillo, Carmen Yessenia (2016)
The Manu parish one of the largest in the Canton Saraguro represents 17% of the total area of the Canton, is located 67km from the cantonal head, has three types of climate such as: warm, moderate and cold. This picturesque parish is dedicated mostly to agriculture, livestock and tourism, is surrounded by mountains where a large natural landscape and own several parcels of crops in the area observed. This parish has a variety of natural and cultural attractions that have not been exploited for tourism because some of them are not able to be visited and others have not had the due diffusion causing the lack thereof. This project seeks to activation of tourism by lifting factsheets of the different attractions of the sector, also it aims to raise awareness about the importance of conservation of attractive, because if these are in poor condition are not safe for tourists. The specific objectives were: To develop the tourist diagnosis of the current situation of Laguna Chinchilla Manu industry belonging to the parish. Senderización design proposal and Señalética Laguna Chinchilla and Socialization of the proposal to the stakeholders. The methodology used for the first specific objective develop the tourist diagnosis of the current situation of Laguna Chinchilla industry consisted of the analytical method enabling the analysis of the environment of the Laguna Chinchilla and the matrix Carla Ricaurte and the tab for inventory attractive tourist MINTUR, to validate the hierarchy and the potential represented in tourism. For the second specific objective To design the proposal Senderización and Señalética Laguna Chinchilla corporate manual tourist signs MINTUR, Cifuentes methodology was used to establish the ability to load and a record made by the tesista for explaining signage. For the third specific objective Socialization of the proposal to stakeholders technique MARPP, the same that consisted of three phases, the first of diagnosis and analysis of the problem, the second planning and the third evaluation of the action was used.